2020
DOI: 10.1002/cb.1902
|View full text |Cite
|
Sign up to set email alerts
|

Word of mouth: How upward social comparisons influence the sharing of consumption experiences

Abstract: An outcome of upward social comparisons that has been largely overlooked is its effect on non-transactional behaviours (i.e., word of mouth). Previous research has identified three different emotional reactions to upward social comparisons: admiration, benign envy and malicious envy. Despite the fact that their effect on consumption has been previously analysed, it remains unclear how these reactions affect word of mouth intention. This study carries out an experimental design that demonstrates that admiration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…It is a common psychological mechanism for individuals to implement unethical behaviors and corrupt behaviors ( Yang et al, 2010a ). The cyber upward social comparison makes people focus on their own shortcomings and produces lower self-assessment, which leads to more negative emotions and more unethical behaviors ( Li, 2018 ; Suárez Vázquez et al, 2021 ). A large number of studies have also confirmed this notion ( Walker et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a common psychological mechanism for individuals to implement unethical behaviors and corrupt behaviors ( Yang et al, 2010a ). The cyber upward social comparison makes people focus on their own shortcomings and produces lower self-assessment, which leads to more negative emotions and more unethical behaviors ( Li, 2018 ; Suárez Vázquez et al, 2021 ). A large number of studies have also confirmed this notion ( Walker et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is the case in situations where feelings of envy come into play. Emotions such as shame and guilt have been highlighted as deterrents of information sharing (Finkenauer and Rimé, 1998), but the effect of envy on information sharing has received little attention (Suárez Vázquez et al , 2020). Frenzen and Nakamoto (1993) originally identified the possible existence of “psychic costs” – as differentiated from economic costs – of information sharing.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In addition, Papathanassis and Knolle (2011) found that the over-representation of positive reviews is viewed as suspicious. Despite these studies, the relationship between eWOM and customers’ self-conscious emotions remained unexplored (Suarez Vazquez et al , 2021). Understanding how eWOM elicits different emotions is critical as customer emotions profoundly influence customer behavior (Hancock et al , 2020).…”
Section: Introductionmentioning
confidence: 99%